Strengthening the Capacity of Micro Enterprises Through Google Business Profile-Based Digitalisation Strategies - Martiyanti, Dwi; Gusti Noorlitaria Achmad; Arvita Rahmawati; Purwadi, Purwadi; Muhammad Wasil (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to enhance the skills of MSME partners of MeykeTalentCookies Balikpapan in utilizing Google Business Profile to support business sustainability. The program was implemented through socialization activities, interactive discussions, and hands-on assistance, with a focus on creating and managing Google Business Profile and Google Maps accounts. Program evaluation employed a qualitative descriptive approach, with data collected through interviews and observations. The evaluation results indicate an improvement in participants’ understanding and skills related to the use of Google Business Profile. This improvement is reflected in the high level of participant engagement and their ability to independently apply and manage the platform. The program is expected to optimize the utilization of existing digital strategies, increase product visibility, and enhance the competitiveness of the MSME partner.